2011
DOI: 10.1038/nature10272
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 proteins act as intracellular receptors for rice Hd3a florigen

Abstract: 'Florigen' was proposed 75 years ago to be synthesized in the leaf and transported to the shoot apex, where it induces flowering. Only recently have genetic and biochemical studies established that florigen is encoded by FLOWERING LOCUS T (FT), a gene that is universally conserved in higher plants. Nonetheless, the exact function of florigen during floral induction remains poorly understood and receptors for florigen have not been identified. Here we show that the rice FT homologue Hd3a interacts with 14-3-3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
774
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(802 citation statements)
references
References 42 publications
23
774
2
3
Order By: Relevance
“…FT and TFL1 are closely related proteins whose opposite function is caused by differences in the external loop (Ahn et al, 2006). A recent study showed that FT forms a so-called "florigen activation complex" together with FD and 14-3-3 proteins (Taoka et al, 2011). Because TFL1 homologs in different species can also bind FD and 14-3-3 (Pnueli et al, 2001;Purwestri et al, 2009;Hanano and Goto, 2011), FvTFL1 may inhibit flowering by competing for binding partners with FvFT1.…”
Section: Regulation Of Fvtfl1 Mrna Expression Controls Photoperiodic mentioning
confidence: 99%
See 1 more Smart Citation
“…FT and TFL1 are closely related proteins whose opposite function is caused by differences in the external loop (Ahn et al, 2006). A recent study showed that FT forms a so-called "florigen activation complex" together with FD and 14-3-3 proteins (Taoka et al, 2011). Because TFL1 homologs in different species can also bind FD and 14-3-3 (Pnueli et al, 2001;Purwestri et al, 2009;Hanano and Goto, 2011), FvTFL1 may inhibit flowering by competing for binding partners with FvFT1.…”
Section: Regulation Of Fvtfl1 Mrna Expression Controls Photoperiodic mentioning
confidence: 99%
“…In contrast, in the SD plant rice, an FT homolog, Heading date3a, is activated when the CO homolog Heading date1 peaks after dusk in SDs (Hayama et al, 2003). After the activation of FT expression, the FT protein moves through the phloem to the shoot apex (Corbesier et al, 2007;Jaeger and Wigge, 2007;Tamaki et al, 2007), where 14-3-3 proteins bridge its interaction with a bZIP transcription factor, FLOWERING LOCUS D (FD; Taoka et al, 2011). The FT/14-3-3/FD complex, in turn, induces flowering by up-regulating the floral meristem identity genes APETALA1 (AP1) and FRUITFULL (FUL; Abe et al, 2005;Wigge et al, 2005).…”
mentioning
confidence: 99%
“…The Hd3a protein moved through a graft into wild-type potato stolons and increased tuber production (Navarro et al, 2011). Hd3a functions in a hexameric floral activation complex (FAC) composed of three homodimers consisting of Hd3a, OsFD, and a 14-3-3 protein that functions as a scaffold (Taoka et al, 2011). Through interactions of FT with a different protein partner that regulates a unique set of targets, the FAC model provides the molecular basis for creating multiple functions for FT beyond flowering (Tsuji and Taoka, 2014).…”
Section: Stsp6a An Ft Ortholog Of Potato Is a Signal For Tuberizationmentioning
confidence: 99%
“…The photoperiod and vernalization pathways converge at the regulation of FT1 (= VRN3 in wheat) (10), which encodes a mobile protein that travels from leaves to the shoot apical meristem (SAM) (11,12). Once in the SAM, FT1 becomes part of a florigen activation complex that binds to the VRN1 promoter, inducing its transcription (13)(14)(15). In common wheat, most genes exist in three copies (homeologs), which are designated using their respective genomes (e.g., VRN-A1, VRN-B1, and VRN-D1).…”
mentioning
confidence: 99%